Guicciardini, Geopolitics and Geohistory - Mallinson, William. author. aut Link
XIII, 151 p. 5 illus., 1 illus. in color.
Keywords: "An amazing counterblast to geopolitics and the realist school of international relations." Professor Vassilis K. Fouskas, University of East London and founding editor, Journal of Balkan and Near Eastern Studies (Routledge) "William Mallinson goes beyond the stereotypes and proposes a fresh and critical look at international relations and its theories: a powerful and thoughtful book based on deep analysis of how history and human nature shape relations between states. A long needed new angle in IR." --Pavel Kanevskiy, Professor of Political Science, Associate Dean, Faculty of Sociology, Lomonosov Moscow State University “Professor Mallinson has written a highly intellectual book on Guiccardini that sheds light on geohistory.” --Leonidas Chrysanthopoulos, Ambassador ad honorem This book demonstrates that geohistory is a more effective concept than geopolitics in understanding inter-state relations, at a time of considerable confusion in world affairs, and that Francesco Guicciardini’s thoughts are an efficient medium to demonstrate not only the inadequacies of geopolitics, but that a geohistorical approach can be a more responsible way of understanding international affairs. The book introduces a fresh approach, based on the individual, on which corporate characteristics and behaviour depend, often in the shape of state interests, which are unable on their own to predict actions driven by human behaviour. The book shows how show mainstream international relations theories are stuck in paradigms, inadequate in explaining why world politics is moving in a direction that nobody could predict even a decade ago. It shows how ideology can blur clear understanding. In short, it represents a new and intellectually refreshing approach and method in understanding, and tackling, the vagaries of relations between states. William Mallinson, a former British diplomat, is professor of Political Ideas and Institutions at Guglielmo Marconi University and a member of the editorial committee of the Journal of Balkan and Near Eastern Studies. He has published numerous books and articles, of which his most recent are Kissinger and the Invasion of Cyprus, and Images in Words: Only History Exists.